Intracellular adhesion molecule 1 plays a key role in acquired immunity to Salmonellosis - Simmons, Cameron (2018)
This study investigated the role of intracellular adhesion molecule 1 (ICAM-1) during Salmonella enterica serovar Typhimurium infection of mice. We show that ICAM-1 is expressed in and around granulomas on day 4 of infection in wild-type mice. However, when naive ICAM-1(-/-) mice were challenged with a sublethal dose of serovar Typhimurium, there were no detectable differences in systemic bacterial burden over the first 9 days of infection compared to wild-type control mice. When mice were immunized with the S. enterica serovar Typhimurium vaccine strain SL2361 and then challenged with the virulent S. enterica serovar Typhimurium strain C5, 100% of the ICAM-1(-/-) mice succumbed to infection, compared to 30% of wild-type mice. T-cell responses, as measured by activation via interleukin-2 production, as well as antibody responses were comparable in the ICAM-1(-/-) and wild-type mice. Following challenge, counts in organs were significantly higher in the ICAM-1(-/-) mice, and histological examination of organs showed pathological differences. Strain SL3261-immunized wild-type mice had cellular infiltrate and normal granuloma formation in the liver and spleen on days 5 and 10 after challenge with strain C5. ICAM-1(-/-) mice had a similar infiltrate on day 5, whereas on day 10 the infiltrate was more widespread and there were fewer macrophages associated with the granulomas. High circulating levels of tumor necrosis factor alpha and gamma interferon, as well as a high burden of strain C5 in the blood, accompanied the differences in histopathology. In this study we show that ICAM-1 plays a critical role during rechallenge of immunized mice with virulent S. enterica serovar Typhimurium.